A guanfacine patch and a preparation method and application thereof

CN118697719BActive Publication Date: 2026-10-13SHENYANG PHARMA UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410195517.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-22
Publication Date
2026-10-13
Estimated Expiration
2044-02-22

AI Technical Summary

Technical Problem

[0006]药物与基质相容性是影响贴剂稳定性的基础,贴剂通常以高载药量为前提,若药物与基质的相容性不佳,容易发生过饱和而引起析晶现象,造成剂量不准确、药物透过能力降低,还会影响压敏胶的黏附性

Benefits of technology

[0038]本发明首先合成了胍法辛与不同有机酸的有机酸盐,以替代胍法辛游离碱,使用含羟基的聚丙烯酸酯压敏胶和抑晶剂,从而防止胍法辛的析晶,提高载药量,使用经皮吸收促进剂,提高胍法辛的经皮透过能力同时实现长效给药。胍法辛72小时累积透过量可达0.7mg/cm2。本贴剂制备剂技术简单、贴剂的稳定性和黏附性良好,使用方便,可以维持3天的药物经皮递送。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004709501540000011
    Figure HDA0004709501540000011
  • Figure HDA0004709501540000012
    Figure HDA0004709501540000012
  • Figure HDA0004709501540000021
    Figure HDA0004709501540000021
Patent Text Reader

Abstract

The application belongs to the technical field of medicine, and relates to a guanfacine patch as well as a preparation method and application thereof. The application provides a guanfacine patch, which aims to improve the medication compliance of patients and improve the bioavailability of the drug. The patch is composed of a backing layer, a drug-loaded pressure-sensitive adhesive layer and an anti-adhesion layer. The drug-loaded pressure-sensitive adhesive layer comprises guanfacine or a pharmaceutically acceptable salt thereof, pressure-sensitive adhesive, crystal inhibitor and transdermal absorption promoter, which effectively avoids drug crystallization, improves the stability and transdermal penetration capacity of the drug. In addition, through specific component ratio and preparation process, the sustained release of guanfacine is realized, and the treatment effect is improved. The application provides a new drug administration mode for the treatment of attention deficit hyperactivity disorder, is especially suitable for children and patients with dysphagia, and has a good clinical application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of pharmaceutical technology and relates to a guanfaxin patch, its preparation method and application. Background Technology

[0002] Attention deficit hyperactivity disorder (ADHD), also known as ADHD, is a common, complex, chronic neurodevelopmental disorder characterized by inattention, hyperactivity, mood swings, and cognitive and social impairments. ADHD typically begins in early childhood and continues into adolescence and adulthood. Individuals with ADHD experience significant learning and social difficulties, severely impacting their daily learning, life, and work, placing a heavy burden on their families and society.

[0003] Medications for ADHD are mainly divided into stimulant and non-stimulant classes. The former, represented by drugs such as methylphenidate, amphetamine, and amphetamine, are effective for most patients and suitable for short-term treatment. However, long-term use can negatively impact children's growth and may lead to drug abuse and dependence. The latter, including atomoxetine, clonidine, and guanfasine, are often used as adjunctive therapy to stimulants for patients who do not respond well to or cannot tolerate the side effects of stimulant treatments. Guanfasine is a non-stimulant ADHD medication, belonging to the class of selective α-2A adrenergic receptor agonists. It acts on postsynaptic α-2A receptors in pyramidal cortical neurons. These receptors are coupled to Gi proteins that inhibit adenylate cyclase, reducing the production of cyclic adenosine monophosphate (cAMP). Guanfasine has a higher affinity for α-2A receptors than for α-2B and α-2C receptors. Compared to clonidine, a similar drug, guanfasine has stronger selectivity for postsynaptic α-2A receptors, thus its enhancing effect on the cerebral cortex is more effective and better tolerated by patients.

[0004] Patents CN201880066618.4, CN201880066613.1, and CN201880066612.7 disclose guanfaxin transdermal therapy systems for transdermal administration, which respectively contain at least one silicone-acrylic hybrid polymer, contain at least one polymer and at least one additive, and contain at least one silicone polymer.

[0005] In 2009, the FDA approved the product name as Guanfaxine extended-release tablets have been officially launched in the United States, demonstrating significant clinical efficacy in treating ADHD in children, adolescents, and adults. This drug is non-addictive and does not cause drug abuse or dependence; compared to similar drugs like clonidine, it has higher selectivity, fewer side effects, and greater safety. However, this formulation has poor compliance among children with ADHD who have difficulty swallowing, and the need for long-term continuous medication for chronic diseases can increase the burden on the patient's gastrointestinal tract. Therefore, developing guanfaxine into a transdermal patch is a worthwhile option to explore. This would not only avoid the first-pass effect of guanfaxine but also improve patient compliance, especially in children, and reduce the frequency of administration.

[0006] Drug-matrix compatibility is fundamental to the stability of patches. Patches are usually designed with high drug loading capacity. If the drug-matrix compatibility is poor, supersaturation can easily occur, leading to crystallization, inaccurate dosage, reduced drug permeability, and also affecting the adhesion of pressure-sensitive adhesives.

[0007] To prevent crystallization of guanfacinol, ion-pairing technology and a highly polar hydroxyl-containing polyacrylate pressure-sensitive adhesive were synthesized, along with a crystallization inhibitor to increase drug-matrix compatibility. To further enhance transdermal drug permeation, a suitable transdermal absorption enhancer was added to ensure optimal transdermal rate. Summary of the Invention

[0008] To address the shortcomings of existing technologies, this invention provides a guanfacin patch; by synthesizing a highly permeable organic acid salt with the drug and organic acid, and by using a hydroxyl-containing polyacrylate pressure-sensitive adhesive and a crystallization inhibitor in combination to prevent drug crystallization, and by adding a transdermal absorption enhancer to ensure the transdermal permeation of guanfacin.

[0009] This invention is achieved through the following technical solution:

[0010] To avoid drug crystallization in guanfacinum patches, the drug is synthesized with organic acids to form highly permeable organic acid salts. At the same time, hydroxyl-containing polyacrylate pressure-sensitive adhesives are used in combination. Crystallization inhibitors are added to the pressure-sensitive adhesives to form hydrogen bonds with the drug organic acid salts to prevent drug crystallization. Transdermal absorption enhancers are added to ensure the transdermal permeation of guanfacinum.

[0011] The guanfasin patch provided by this invention comprises a backing layer, a drug-loaded pressure-sensitive adhesive layer, and an anti-adhesive layer. The drug-loaded pressure-sensitive adhesive layer contains an organic acid salt pressure-sensitive adhesive formed from the drug and an organic acid, a crystallization inhibitor, and a transdermal absorption enhancer. Compared to commercially available pressure-sensitive adhesives, a hydroxyl-containing polyacrylate pressure-sensitive adhesive preferably exhibits better compatibility with the crystallization inhibitor.

[0012] Furthermore, the drug-loaded pressure-sensitive adhesive layer comprises guanethidine free base or a pharmaceutically acceptable salt thereof, pressure-sensitive adhesive, crystal inhibitor, and transdermal absorption enhancer.

[0013] Furthermore, the pharmaceutically acceptable salts of the guanethidine are one or more of the following: guanethidine oleate, guanethidine decanoate, guanethidine laurate, guanethidine octanoate, guanethidine linoleate, guanethidine geraniol, guanethidine myristate, guanethidine lactate, or guanethidine hexanoate.

[0014] Furthermore, the transdermal absorption enhancer is an amine, amide, fatty acid and its ester, alcohol, sulfoxide, surfactant, amino acid and its ester, terpene, ether or phospholipid compound, preferably one or more of isopropyl myristate, diethylene glycol monoethyl ether, glyceryl monooleate, and azone menthol.

[0015] Furthermore, the crystallization inhibitor is cellulose and its derivatives, methacrylate and its derivatives, polyvinylpyrrolidone and its derivatives, copovidone, crosslinked povidone or polyethylene glycol and its copolymers;

[0016] Furthermore, the material selected for the backing layer is polyurethane film, polyethylene single-layer film, aluminum-polyethylene composite film, polyester composite film, polyolefin single-layer film, ethylene vinyl acetate film, or elastic non-woven fabric.

[0017] Furthermore, the material selected for the anti-stick layer is selected from polyester film or paper coated with fluoropolymer and treated with silicone oil for anti-sticking or fluorine-containing polyester film.

[0018] Furthermore, the weight of the ionic liquid of the guanidine free base or its pharmaceutically acceptable salt accounts for 1.0-35 wt% of the total weight of the drug-loaded pressure-sensitive adhesive layer, the pressure-sensitive adhesive accounts for 50-90 wt% of the total weight of the drug-loaded pressure-sensitive adhesive layer, the crystallization inhibitor accounts for 5.0-25 wt% of the drug-loaded pressure-sensitive adhesive layer, and the transdermal absorption enhancer accounts for 0-17 wt% of the total weight of the drug-loaded pressure-sensitive adhesive layer, totaling 100 wt%.

[0019] Furthermore, the pressure-sensitive adhesive is a hydroxyl-containing polyacrylate pressure-sensitive adhesive; the hydroxyl-containing polyacrylate pressure-sensitive adhesive is copolymerized from three monomers: methyl acrylate, isooctyl acrylate, and hydroxyethyl acrylate. The proportions of the above three monomers range from 25.0-27.3 wt% for methyl acrylate, 50.0-54.5 wt% for isooctyl acrylate, and 18.2-25.0 wt% for hydroxyethyl acrylate, totaling 100 wt%.

[0020] Furthermore, the preferred proportions of the three monomers contained in the pressure-sensitive adhesive are methyl acrylate 25.8-26.3 wt%, isooctyl acrylate 51.7-52.6 wt%, and hydroxyethyl acrylate 21.0-22.4 wt%, totaling 100 wt%.

[0021] Furthermore, the amount of the transdermal absorption enhancer is preferably 7.8-11.4 wt% of the total weight of the drug-loaded pressure-sensitive adhesive layer.

[0022] Furthermore, in the pharmaceutically acceptable salts of guanethidine, the molar ratio of the guanethidine free base to different organic acids is (0.5:1)-(2:1), preferably 1:1.

[0023] Furthermore, the pharmaceutically acceptable salt of guanethidine is synthesized by the following method:

[0024] Dissolve the free base of guanidine octanoate in a mixed solvent of acetone and ethanol; add an organic acid in molar ratio; stir evenly at room temperature for 2-4 hours, and evaporate the solvent to obtain guanidine octanoate organic acid salt; the organic acid is one or more of oleic acid, decanoic acid, lauric acid, octanoic acid, linoleic acid, geraniic acid, myristic acid, lactic acid or hexanoic acid.

[0025] Furthermore, the weight of the ionic liquid of the guanethidine free base or its pharmaceutically acceptable salt accounts for 1.0-35 wt% of the total weight of the drug-loaded pressure-sensitive adhesive layer.

[0026] The pressure-sensitive adhesive used is a hydroxyl-containing polyacrylate pressure-sensitive adhesive, which is copolymerized from three monomers: methyl acrylate, isooctyl acrylate, and hydroxyethyl acrylate. The proportions of the three monomers range from 25.0-27.3% methyl acrylate, 50.0-54.5% isooctyl acrylate, and 18.2-25.0% hydroxyethyl acrylate, preferably 25.8-26.3% methyl acrylate, 51.7-52.6% isooctyl acrylate, and 21.0-22.4% hydroxyethyl acrylate.

[0027] Furthermore, the hydroxyl-containing polyacrylate pressure-sensitive adhesive is copolymerized by the following method: three monomers are taken in proportion, using ethyl acetate (50-70%, w / w) as solvent, and azobisisobutyronitrile (0.2-1%, w / w) as initiator at 50-80℃ for 6-14 hours to obtain the hydroxyl-containing polyacrylate pressure-sensitive adhesive. Its weight-average molecular weight is between 400,000 Da and 700,000 Da, its polydispersity index is between 1 and 3, and its solid content is between 35-50%.

[0028] The hydroxyl-containing polyacrylate pressure-sensitive adhesive of the present invention increases the interaction between the drug and the drug by introducing the functional monomer hydroxyethyl acrylate, thereby increasing the compatibility between the drug and the pressure-sensitive adhesive matrix.

[0029] Furthermore, the crystallization inhibitor is preferably polyvinylpyrrolidone, polyvinylcaprolactam-polyvinyl acetate-polyethylene glycol graft copolymer, or vinylpyrrolidone-vinyl acetate copolymer.

[0030] Furthermore, the anti-crystallization agent is preferably polyvinylpyrrolidone; its amount accounts for 5.0-25.0 wt% of the total weight of the pressure-sensitive adhesive.

[0031] The crystallization inhibitor polyvinylpyrrolidone described in this invention can interact with the hydroxyl-containing polyacrylate pressure-sensitive adhesive to form a uniform pressure-sensitive adhesive matrix.

[0032] Furthermore, the transdermal absorbent is preferably isopropyl myristate; its amount accounts for 7.8-11.4 wt% of the total weight of the drug-loaded pressure-sensitive adhesive layer.

[0033] The present invention also provides a method for preparing the guanfacinol patch, comprising the following steps:

[0034] Guanfacin free base or its organic acid salt is dissolved in an organic solvent. After complete dissolution, a crystal inhibitor and a transdermal absorption promoter are added and dispersed in a solvent-containing hydroxyl polyacrylate pressure-sensitive adhesive. After thorough stirring, it is transferred and coated onto an anti-adhesive layer, dried at 40-70℃ for 10-20 minutes, covered with a backing layer, and die-cut into a certain size to obtain guanfacin patch.

[0035] In the guanfacinol patch, the thickness of the drug-loaded pressure-sensitive adhesive layer is 30-120 μm.

[0036] The present invention also provides the use of the guanfasine patch in the preparation of a medicament for treating attention deficit hyperactivity disorder.

[0037] The beneficial effects of this invention are:

[0038] This invention first synthesizes organic acid salts of guanifacine and different organic acids to replace the free base of guanifacine. It then uses hydroxyl-containing polyacrylate pressure-sensitive adhesives and crystallization inhibitors to prevent crystallization of guanifacine and increase drug loading. Finally, it employs transdermal absorption enhancers to improve the transdermal permeability of guanifacine while achieving long-acting administration. The cumulative permeation of guanifacine over 72 hours can reach 0.7 mg / cm³. 2 This patch has a simple preparation technology, good stability and adhesion, is easy to use, and can maintain transdermal drug delivery for 3 days. Attached Figure Description

[0039] Figure 1 The organic acid salts were screened based on cumulative permeation for the guanethidine and its organic acid salt transdermal absorption patches prepared in Examples 6-11.

[0040] Figure 2 This represents the maximum drug loading in Examples 20, 23-26.

[0041] Figure 3 This is an evaluation of the crystal-inhibiting effect of various types of crystal inhibitors in Examples 17-22.

[0042] Figure 4 The types of penetration enhancers were screened for the guanfaxin patches prepared in Examples 20 and 23-26 based on the cumulative permeation amount.

[0043] Figure 5 The guanfaxin patch (9cm) prepared in Example 23 2 Blood concentration-time curve of 12mg in rabbits. Detailed Implementation

[0044] The present invention is illustrated in more detail by way of the following examples. It should be clear that the present invention is by no means limited to the embodiments, or is only exemplified by the embodiments.

[0045] Example 1

[0046] Dissolve 0.1 mol of guanidine octanoic acid free base in 40 ml of a mixed solvent of acetone and ethanol. Add 0.1 mol of oleic acid while stirring, and continue stirring for 4 hours. Then, evaporate the solvent by rotary evaporation to obtain guanidine octanoic acid oleate.

[0047] Example 2

[0048] Dissolve 0.1 mol of guanidine octanoic acid free base in 40 ml of a mixed solvent of acetone and ethanol. Add 0.1 mol of lauric acid while stirring, and continue stirring for 4 hours. Then, evaporate the solvent by rotary evaporation to obtain guanidine octanoic acid laurate.

[0049] Example 3

[0050] Dissolve 0.1 mol of guanidine octanoic acid free base in 40 ml of a mixed solvent of acetone and ethanol. Add 0.1 mol of n-octanoic acid while stirring, and continue stirring for 4 hours. Then, evaporate the solvent by rotary evaporation to obtain guanidine octanoic acid salt.

[0051] Example 4

[0052] Dissolve 0.1 mol of guanethidine free base in 40 ml of a mixed solvent of acetone and ethanol. Add 0.1 mol of geraniol while stirring, and continue stirring for 4 hours. Then, evaporate the solvent by rotary evaporation to obtain guanethidine geraniol.

[0053] Example 5

[0054] Dissolve 0.1 mol of guanidine octanoic acid free base in 40 ml of a mixed solvent of acetone and ethanol. Add 0.1 mol of lactic acid while stirring, and continue stirring for 4 hours. Then, evaporate the solvent by rotary evaporation to obtain guanidine octanoic acid.

[0055] Example 6

[0056] Disperse 0.1 mmol of guanidine alkali in 2 g of polyacrylate pressure-sensitive adhesive and mix thoroughly. Coat evenly on the release layer and dry at 50°C for 15 min. Then cover with a backing material including PVC or non-woven fabric and die-cut to make a patch with a thickness of 80 μm.

[0057] Example 7

[0058] Disperse 0.1 mmol of guanidine octooleate in 2 g of polyacrylate pressure-sensitive adhesive and mix thoroughly. Coat evenly on the release layer and dry at 50°C for 15 min. Then cover with a backing material including PVC or non-woven fabric and die-cut to make a patch with a thickness of 80 μm.

[0059] Example 8

[0060] Disperse 0.1 mmol guanidine laurate in 2 g polyacrylate pressure-sensitive adhesive and mix thoroughly. Coat evenly on the release layer and dry at 50°C for 15 min. Then cover with a backing material including PVC or non-woven fabric and die-cut to make a patch with a thickness of 80 μm.

[0061] Example 9

[0062] Disperse 0.1 mmol guanidine octanoate in 2 g polyacrylate pressure-sensitive adhesive and mix thoroughly. Coat evenly on the release layer and dry at 50°C for 15 min. Then cover with a backing material including PVC or non-woven fabric, and die-cut to make a patch with a thickness of 80 μm.

[0063] Example 10

[0064] Disperse 0.1 mmol of guanethidine leaf salt in 2 g of polyacrylate pressure-sensitive adhesive and mix thoroughly. Coat evenly on the release layer and dry at 50°C for 15 min. Then cover with a backing material including PVC or non-woven fabric, and die-cut to make a patch with a thickness of 80 μm.

[0065] Example 11

[0066] Disperse 0.1 mmol guanidine lactate in 2 g polyacrylate pressure-sensitive adhesive and mix thoroughly. Coat evenly on the release layer and dry at 50°C for 15 min. Then cover with a backing material including PVC or non-woven fabric and die-cut to make a patch with a thickness of 80 μm.

[0067] Example 12

[0068] The maximum drug loading capacity in pressure-sensitive adhesive was determined by dispersing an appropriate amount of guanidine octooleate in a silicone pressure-sensitive adhesive containing 2g of silicone. Mix thoroughly in 4202 and determine the maximum drug loading.

[0069] Example 13

[0070] The maximum drug loading capacity in pressure-sensitive adhesive was determined by dispersing an appropriate amount of guanidine octooleate in a pressure-sensitive adhesive containing 2g of polyisobutylene. Mix thoroughly in 87-6908 and determine the maximum drug loading.

[0071] Example 14

[0072] The maximum drug loading capacity in pressure-sensitive adhesive was determined by dispersing an appropriate amount of guanidine octooleate in a pressure-sensitive adhesive containing 2g of polyacrylate. Mix thoroughly in 87-4098 and determine the maximum drug loading.

[0073] Example 15

[0074] The maximum drug loading capacity in pressure-sensitive adhesive was determined by dispersing an appropriate amount of guanidine octooleate in a pressure-sensitive adhesive containing 2g of polyacrylate. Mix thoroughly in 87-2287 and determine the maximum drug loading.

[0075] Example 16

[0076] To determine the maximum drug loading in pressure-sensitive adhesive, an appropriate amount of guanidine octoate was dispersed in a pressure-sensitive adhesive containing 2g of hydroxyl-containing polyacrylate and thoroughly mixed, and the maximum drug loading was determined.

[0077] The maximum drug loading results for Examples 12-16 are shown in Table 1:

[0078] Table 1. Maximum drug loading of guanifacin or its organic acid salts in various types of pressure-sensitive adhesives

[0079] Maximum drug loading (%) 0.5±0.3 0.7±0.3 3.2±0.4 4.1±0.5 7.3±0.3

[0080] The experimental results show that when hydroxyl-containing polyacrylate pressure-sensitive adhesive is used as the pressure-sensitive adhesive for the patch, the drug loading capacity is the largest. Therefore, hydroxyl-containing polyacrylate pressure-sensitive adhesive is selected as the pressure-sensitive adhesive matrix.

[0081] Example 17

[0082] 0.5g of guanidine octooleate was dispersed in hydroxyl-containing polyacrylate pressure-sensitive adhesive and mixed thoroughly. 0.1g of polyvinylpyrrolidone was added and after thorough mixing, it was evenly coated onto the release layer. After drying at 50°C for 15 minutes, it was covered with a backing material including PVC or non-woven fabric, and then die-cut to make a patch with a thickness of 80μm. Drug crystallization was observed.

[0083] Example 18

[0084] Disperse 0.5g of guanidine octooleate in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mix thoroughly. Add 0.1g of... After thorough mixing, the mixture is evenly coated onto the release layer and dried at 50°C for 15 minutes. Then, it is covered with a backing material including PVC or non-woven fabric, punched, and made into a patch with a thickness of 80 μm. Drug crystallization is then observed.

[0085] Example 19

[0086] Disperse 0.5g of guanidine octooleate in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mix thoroughly. Add 0.1g of copovidone and after thorough mixing, coat evenly onto the release layer. After drying at 50°C for 15 minutes, cover with a backing material including PVC or non-woven fabric, and punch-cut to make a patch with a thickness of 80μm. Observe drug crystallization.

[0087] Example 20

[0088] Disperse 0.5g of guanidine octooleate in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mix thoroughly. Add 0.2g of polyvinylpyrrolidone and after thorough mixing, coat evenly onto the release layer. After drying at 50℃ for 15min, cover with a backing material including PVC or non-woven fabric, and punch-cut to make a patch with a thickness of 80μm. Observe drug crystallization.

[0089] Example 21

[0090] Disperse 0.5g of guanidine octooleate in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mix thoroughly. Add 0.2g of... After thorough mixing, the mixture is evenly coated onto the release layer and dried at 50°C for 15 minutes. Then, it is covered with a backing material including PVC or non-woven fabric, punched, and made into a patch with a thickness of 80 μm. Drug crystallization is then observed.

[0091] Example 22

[0092] Disperse 0.5g of guanidine octooleate in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mix thoroughly. Add 0.2g of copovidone and after thorough mixing, coat evenly onto the release layer. After drying at 50°C for 15 minutes, cover with a backing material including PVC or non-woven fabric, and punch-cut to make a patch with a thickness of 80μm. Observe drug crystallization.

[0093] The drug crystallization conditions of Examples 17-22 are shown in Table 2 and Figure 3 :

[0094] Table 2 Evaluation of the crystal-inhibiting effect of various types of crystal inhibitors

[0095] Whether crystallization occurs yes yes yes no yes yes

[0096] Experimental results show that when 0.2g of polyvinylpyrrolidone is added, guanidine octooleate in the patch does not crystallize out.

[0097] Example 23

[0098] 0.5g of guanidine octooleate was dispersed in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mixed thoroughly. 0.2g of polyvinylpyrrolidone and 0.16g of isopropyl myristate were added and mixed thoroughly. The mixture was then evenly coated onto an anti-adhesive layer and dried at 50°C for 15 minutes. The mixture was then covered with a backing material including PVC or non-woven fabric, die-cut, and made into a patch with a thickness of 80μm. Drug crystallization was then observed.

[0099] Example 24

[0100] 0.5g of guanidine octooleate was dispersed in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mixed thoroughly. 0.2g of polyvinylpyrrolidone and 0.16g of diethylene glycol monoethyl ether were added. After thorough mixing, the mixture was evenly coated onto the release layer and dried at 50°C for 15 minutes. Then, it was covered with a backing material including PVC or non-woven fabric, and die-cut to make a patch with a thickness of 80μm. Drug crystallization was observed.

[0101] Example 25

[0102] 0.5g of guanidine octooleate was dispersed in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mixed thoroughly. 0.2g of polyvinylpyrrolidone and 0.16g of glyceryl monooleate were added and mixed thoroughly. The mixture was then evenly coated onto an anti-adhesive layer and dried at 50°C for 15 minutes. The mixture was then covered with a backing material including PVC or non-woven fabric, die-cut, and made into a patch with a thickness of 80μm. Drug crystallization was then observed.

[0103] Example 26

[0104] 0.5g of guanidine octooleate was dispersed in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive and mixed thoroughly. 0.2g of polyvinylpyrrolidone and 0.16g of menthol were added and mixed thoroughly. The mixture was then evenly coated onto an anti-adhesive layer and dried at 50°C for 15 minutes. The mixture was then covered with a backing material including PVC or non-woven fabric and die-cut to form a patch with a thickness of 80μm. Drug crystallization was then observed.

[0105] Experimental Example 1

[0106] In vitro percutaneous test:

[0107] A horizontal single-chamber diffusion cell was used, with fresh rat abdominal skin as the transdermal barrier and pH 6.4 phosphate buffer as the receiving medium. During the experiment, a magnetic stirrer was used continuously at a speed of 300-400 rpm, and the system temperature was maintained at 32℃. The cumulative permeation of the guanethidine patch over 24 hours or 72 hours was measured.

[0108] The results of screening for organic acid salts in the guanidine octanoic acid free base and organic acid salt transdermal absorption patches prepared in Examples 6-11, based on cumulative permeation, are shown in the figure. Figure 1 .

[0109] Conclusion: Guanfacin forms salts with organic acids, which can significantly enhance the transdermal permeability of guanfacin, and the transdermal permeability of guanfacin is the highest when guanfacin oleate (Example 6) is used.

[0110] Examples 17-22 show the preparation of guanidine octyl oleate patches containing different types and amounts of crystal inhibitors. The results of screening for different types and amounts of crystal inhibitors, using the absence of crystallization as the criterion, are shown in [the original text]. Figure 3 .

[0111] The results of screening for penetration enhancers based on cumulative permeation amount for the guanfacinoxan patches prepared in Examples 20 and 23-26 are shown below. Figure 4 .

[0112] Conclusion: Compared with the group without the promoter, the promoters menthol, glyceryl monooleate, and diethylene glycol monoethyl ether did not significantly increase the cumulative permeation of guanethidine. Isopropyl myristate (Example 23) increased the cumulative permeation the most. Therefore, isopropyl myristate is preferred as the transdermal absorption promoter.

[0113] Experimental Example 2

[0114] Guanfacinoxate patches were prepared using the method described in Example 23, with a patch thickness of 80 μm. Ten male Japanese white rabbits were randomly divided into two groups. One group received the patch (Example 23) via pre-shaved abdominal injection, which was removed after 72 hours. The other group received a saline solution of guanfacinoxate hydrochloride via intravenous injection in the ear vein. Blood samples were collected from the ear vein at predetermined time points to determine the blood concentration of guanfacinoxate in the rabbits. The results are shown below. Figure 5 .

[0115] Conclusion: In the pharmacokinetic study in rabbits, the blood drug concentration of the patch was relatively stable and could maintain stable drug administration for 72 hours.

Claims

1. A method for preparing a guanfacinol patch, characterized in that, Follow these steps: Disperse 0.5g of guanidine octooleate in 2g of hydroxyl-containing polyacrylate pressure-sensitive adhesive, add 0.2g of polyvinylpyrrolidone and 0.16g of isopropyl myristate, mix evenly and coat onto the release layer, dry at 50°C for 15 minutes, and then cover with a backing material including PVC or non-woven fabric.

2. The method for preparing the guanfacinol patch according to claim 1, characterized in that, The thickness of the drug-loaded pressure-sensitive adhesive layer is 80 μm.

3. The method for preparing the guanfacinol patch according to claim 1, characterized in that, The molar ratio of guanethidine to oleic acid in the guanethidine oleate is (0.5:1)-(2:1).

4. The method for preparing the guanfacinol patch according to claim 3, characterized in that, The molar ratio of guanethidine to oleic acid in the guanethidine oleate is 1:

1.

5. The method for preparing the guanfacinol patch according to claim 1, characterized in that, The hydroxyl-containing polyacrylate pressure-sensitive adhesive is copolymerized from three monomers: methyl acrylate, isooctyl acrylate, and hydroxyethyl acrylate. The proportions of the three monomers are 25.0-27.3 wt% methyl acrylate, 50.0-54.5 wt% isooctyl acrylate, and 18.2-25.0 wt% hydroxyethyl acrylate, totaling 100 wt%.

6. The method for preparing the guanfacinol patch according to claim 5, characterized in that, The proportions of the three monomers range from 25.8-26.3 wt% for methyl acrylate, 51.7-52.6 wt% for isooctyl acrylate, and 21.0-22.4 wt% for hydroxyethyl acrylate, totaling 100 wt%.

7. The use of a guanafacine patch obtained by the preparation method according to any one of claims 1-6 in the preparation of a medicament for treating attention deficit hyperactivity disorder.

Citation Information

Patent Citations

  • Transdermal therapeutic system for transdermal administration of guanfacine comprising at least one additive

    CN111447926B

  • Transdermal therapeutic system for transdermal administration of guanfacine comprising silicone polymer

    CN111465392A

  • Transdermal therapeutic system for the transdermal administration of guanfacine comprising a silicone acrylic hybrid polymer

    CN111491621A

  • Rotigotine percutaneous absorption patch, and preparation and application thereof

    CN110638792A

  • Guanfacine transdermal patch and preparation method thereof

    CN117379398A